(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2017)
A field trial was carried out with rice (BRRI 64) grown in saline soil at Kuakata of Patuakhali District to evaluate the potential of rice straw, rice hull and saw dust each applied at the rates of 0, 4, 8 t ha-1 in moist and saturated conditions. Growth parameters and yield of rice were found to increase significantly (p ≤ 0.05) with the increased rates regardless of kinds of organic treatments under both the conditions. The highest plant heights (89 cm in moist and 101 cm in saturated condition) were recorded at maturity in the treatment, which received the combination (RH8RS8SD8) of highest rates of these 3 organic amendments. The lowest plant heights (73 cm in moist and 77 cm in saturated) were recorded in control condition (RH0RS0SD0). The maximum numbers of tillers were observed in RH8RS8SD8 and RH8RS4SD8 followed by RH8RS8SD4, RH8RS4SD4 and RH4RS8SD8 treatments at saturated condition. The straw dry matter and grain yields of rice were also found to vary significantly (p ≤ 0.05) due to single application of rice hull, rice straw, saw dust and moisture conditions but their combined effects were found to be significantly better at the higher levels. The highest grain yield (6.6 t ha-1) was recorded in RH8RS8SD8 treatment followed by RH8RS8SD4, RH8RS4SD8, RH8RS4SD4 and RH4RS8SD8 at saturated condition. Growth and yield of rice were attained better at saturated condition than that of the moist soil. Asiat. Soc. Bangladesh, Sci. 43(2): 197-206, December 2017